Paraquat increases connective tissue growth factor expression and impairs lung fibroblast proliferation and viscoelasticity. (December 2014) - Zhang, N; Xie, Y-P; Pang, L; Zang, X-X; Wang, J; Shi, D; Wu, Y; Liu, X-L; Wang, G-H
This in vitro study was designed to investigate the molecular mechanisms of paraquat-induced damage using cultured human fetal lung fibroblasts (MRC-5 cells), in order to promote the development of improved therapies for paraquat poisoning. Paraquat's effects on proliferation were examined by flow cytometry, on viscoelasticity by the micropipette aspiration technique, and on connective tissue growth factor (CTGF) expression by real-time polymerase chain reaction and enzyme-linked immunosorbent assay. Paraquat was found to significantly reduce the proliferation index of MRC-5 cells in a concentration-dependent manner ( p < 0.05) and to significantly impair the viscoelastic properties in a time-independent manner ( p < 0.05). Exposure to paraquat led to a significant and time-dependent increase in CTGF expression ( p < 0.05) and induced changes in the morphology and biomechanical characteristics of the MRC-5 cells. These findings not only provide novel insights into the mechanisms of paraquat-induced lung fibrosis but may represent useful targets of improved molecular-based therapies for paraquat poisoning.